2013
DOI: 10.4103/0971-9784.119161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left internal mammary artery diameter before and after left stellate ganglion block

Abstract: LSGB significantly increased the LIMA diameter. The LSGB can be considered as an alternative to topical and systemic vasodilators for reducing vasospasm of LIMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…At the same time, it can enhance the defense function and prevent nerve damage (Boas, 1998). SGB can reduce norepinephrine (Mulvaney et al, 2010) and prostaglandins in the brain and plasma, improve ischemic, anoxic and metabolic abnormalities in local tissues, and remove inflammatory mediators by increasing local blood circulation (Park et al, 2010; Gopal et al, 2013; Kim et al, 2013). SGB can also significantly reduce the cortisol, aldosterone, angiotensin-2, 5-hydroxytryptamine and substance P in the blood of patients with pain (Wang et al, 2005; Jeon, 2016), change the lymphocyte subsets and NK cell activity (Yokoyama et al, 2000), inhibit the proinflammatory cytokines IL-1β, IL-6 and TNF-α, regulate the early inflammation responses (Liu et al, 2013), and promote nerve repair.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it can enhance the defense function and prevent nerve damage (Boas, 1998). SGB can reduce norepinephrine (Mulvaney et al, 2010) and prostaglandins in the brain and plasma, improve ischemic, anoxic and metabolic abnormalities in local tissues, and remove inflammatory mediators by increasing local blood circulation (Park et al, 2010; Gopal et al, 2013; Kim et al, 2013). SGB can also significantly reduce the cortisol, aldosterone, angiotensin-2, 5-hydroxytryptamine and substance P in the blood of patients with pain (Wang et al, 2005; Jeon, 2016), change the lymphocyte subsets and NK cell activity (Yokoyama et al, 2000), inhibit the proinflammatory cytokines IL-1β, IL-6 and TNF-α, regulate the early inflammation responses (Liu et al, 2013), and promote nerve repair.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] LSGB also has been shown to cause vasodilatation of LITA. [ 9 10 ] Majority of the vasodilatory effects on LITA are attained through endothelial expression of nitric oxide and blockade of alpha-receptors or receptors of vasoactive agents such as thromboxane-A2, endothelin-1, prostaglandin-II, adenosine, and angiotensin II. Which pathway among them provides maximum vasodilatory effect still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Some of the studies demonstrated vasodilatory effects of sympatholysis through regional anesthesia techniques such as thoracic epidural anesthesia (TEA)[ 8 ] and left stellate ganglion blockade (LSGB) on LITA flow and diameter, respectively. [ 9 10 ] LSGB also has been shown to improve flow in free radial artery graft. [ 11 ] As various agents used for vasodilatation of arterial grafts differ in their actions, combination therapy has been advocated by some of the investigators to increase blood flow in the grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Left IMA diameter has been measured at the second (2.56±0.39 mm), third (2.46±0.38 mm), fourth (2.39±0.38 mm) and fifth (2.35±0.38 mm) rib level, respectively. [5] In addition, the right IMA and vein are larger than the left in all intercostal spaces. [6] It is a rare occurrence when a left IMA originates from the distal subclavian artery.…”
Section: Anatomymentioning
confidence: 98%